2012
DOI: 10.1096/fj.12-213801
|View full text |Cite
|
Sign up to set email alerts
|

Orai3 is an estrogen receptor α‐regulated Ca 2+ channel that promotes tumorigenesis

Abstract: Store-operated Ca(2+) entry (SOCE) encoded by Orai1 proteins is a ubiquitous Ca(2+)-selective conductance involved in cellular proliferation and migration. We recently described up-regulation of Orai3 channels that selectively mediate SOCE in estrogen receptor α-expressing (ERα(+)) breast cancer cells. However, the connection between ERα and Orai3 and the role of Orai3 in tumorigenesis remain unknown. Here, we show that ERα knockdown decreases Orai3 mRNA (by ∼63%) and protein (by ∼44%) with no effect on Orai1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
181
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(198 citation statements)
references
References 45 publications
14
181
0
3
Order By: Relevance
“…73 Ectopic expression of Orai3 in these ER − breast cancer cells results in a smaller thapsigargin-activated SOCE and its potentiation by 2-APB (Fig. 2B), suggesting functional activation of Orai3-mediated SOCE in these cells (potentiation by 2-APB is a characteristic of SOCE mediated by Orai3 [58][59][60][61][62] 25,26 which is potentiated by addition of 30 μM 2-APB to the bath solution (Fig. 2C).…”
Section: Orai3 In Breast Cancermentioning
confidence: 98%
See 4 more Smart Citations
“…73 Ectopic expression of Orai3 in these ER − breast cancer cells results in a smaller thapsigargin-activated SOCE and its potentiation by 2-APB (Fig. 2B), suggesting functional activation of Orai3-mediated SOCE in these cells (potentiation by 2-APB is a characteristic of SOCE mediated by Orai3 [58][59][60][61][62] 25,26 which is potentiated by addition of 30 μM 2-APB to the bath solution (Fig. 2C).…”
Section: Orai3 In Breast Cancermentioning
confidence: 98%
“…64 Data from our lab showed that SOCE mediated through Orai3 is required for activation of pro-proliferative and pro-migratory pathways; Orai3 knockdown inhibited NFAT transcriptional activity, as well as Ca 2+ -dependent phosphorylation of ERK1/2 and focal adhesion kinase (FAK). 26 As mentioned above, STIM1 and Orai1 were implicated in mediating breast cancer cell migration in vitro using ER − MBA-MD231 breast cancer cells as well as in mediating metastasis in vivo in immune-compromised mice. 19 Although STIM1 and Orai1 knockdown result in inhibition of ER -breast cancer metastasis in nude mice, their potential use as therapeutic targets is questionable since functional STIM1/Orai1-mediated CRAC pathway is essential for proper immunological responses.…”
mentioning
confidence: 88%
See 3 more Smart Citations